Composite adsorbent, preparation method and application in field of hydrogen recovery
By designing the honeycomb structure and stacked structure of the composite adsorbent, the problems of low selectivity of adsorbents, limited adsorption capacity and poor regeneration performance in the prior art are solved, efficient hydrogen recovery and impurity removal are achieved, and the purity and efficiency of hydrogen recovery are improved.
Patent Information
- Application Number
- CN202510299883.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing hydrogen recovery technology, the adsorbent has low selectivity for impurities in hydrogen-rich exhaust gas, limited adsorption capacity, and poor regeneration performance, which makes it difficult for the hydrogen recovery efficiency and purity to meet industrial needs.
A composite adsorbent is designed, adopting a honeycomb structure, with the internal diffusion path controlled within the range of 0.1~0.3mm. The active adsorbent material is fixed through the resin material to form a stacked structure of a dehydrated bed, an O2 adsorbent bed, a CO2 adsorbent bed and a CO adsorbent bed, which improves the specific surface area and pore structure stability of the adsorbent.
It significantly improves the recovery purity and recovery rate of hydrogen, enhances the adsorption performance of impurities, extends the service life of the adsorbent, and reduces the preparation cost.
Smart Images

Figure CN119793140A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen recovery, and in particular relates to a composite adsorbent, a preparation method of the adsorbent and application of the composite adsorbent in the field of hydrogen recovery. Background Art
[0002] In many industrial production processes such as chemical industry, petroleum refining, coal chemical industry, a large amount of hydrogen-rich tail gas is generated. For example, in catalytic reforming, hydrocracking, coke oven gas treatment and other processes, these hydrogen-rich tail gases contain not only hydrogen, but also impurities such as carbon monoxide, carbon dioxide, methane, nitrogen, water vapor and a small amount of hydrogen sulfide. As an important clean energy and chemical raw material, hydrogen has a wide range of application prospects. Recovering high-purity hydrogen from hydrogen-rich tail gas is of great significance for improving resource utilization, reducing production costs and reducing environmental pollution.
[0003] At present, the technologies used to separate hydrogen mainly include cryogenic separation, membrane separation and pressure swing adsorption. The cryogenic separation method requires large equipment investment, high energy consumption and complex operation; although the membrane separation method has relatively simple equipment, the cost of the membrane is relatively high, and the separation efficiency and selectivity are limited by the membrane material. Pressure swing adsorption is widely used because of its advantages such as simple process, flexible operation, low energy consumption and high product purity. However, when the existing adsorbents are used to treat hydrogen-rich tail gas, there are problems such as limited impurity adsorption capacity, low selectivity and poor regeneration performance, which makes it difficult for hydrogen recovery efficiency and purity to meet the higher requirements of industrial production. Therefore, the development of an efficient hydrogen-rich tail gas adsorbent has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0004] In view of the problems existing in the above-mentioned prior art, the object of the present invention is to provide an adsorbent for hydrogen-rich tail gas, which has high adsorption capacity, high selectivity and good regeneration performance for impurities in hydrogen-rich tail gas, and can effectively improve the recovery purity and recovery rate of hydrogen.
[0005] According to a first aspect of the present invention, a composite adsorbent is provided, wherein the two ends of the composite adsorbent are dehydration beds, and the middle part is composed of at least one adsorbent group connected end to end in sequence, and each adsorbent group is distributed with an O2 adsorption bed, a CO2 adsorption bed and a CO adsorption bed in sequence from the direction of gas inlet to outlet; compared with the total volume of the composite adsorbent, the dehydration beds at the two ends account for a total volume of 30-40%, the O2 adsorption bed accounts for 30-40%, the CO2 adsorption bed accounts for 10-20%, and the CO adsorption bed accounts for 10-20%; the composite adsorbent is honeycomb-shaped, with an internal diffusion distance of 0.1-0.3 mm and a porosity of 50-70%.
[0006] The dehydration bed and adsorption bed in the above-mentioned composite adsorbent are made by fixing the adsorbent material with impurity gas adsorption properties in the resin. By adjusting the profile and internal structure of the resin skeleton, the adsorbent material can also be flexibly regulated in its distribution state. In the existing pressure swing adsorption technology, adsorbents are mostly granular, which has the advantages of simple preparation process and easy disassembly and assembly. However, studies have shown that the diameter of hydrogen molecules is relatively small, and adsorbents with higher porosity and appropriate pore size distribution are conducive to the rapid and efficient adsorption of hydrogen molecules. Therefore, the present invention is designed to provide a composite adsorbent with a honeycomb structure, which can effectively reduce the bed resistance of the adsorbent, increase the rate and efficiency of gas passing through the adsorption bed, shorten the internal diffusion path, and thus improve the efficiency and quality of hydrogen purification. In the complex process of gas adsorption, the adsorption rate on the adsorbent surface and the diffusion rate in the pores are usually faster, however, internal diffusion, that is, the diffusion process from the adsorbent surface to its interior, has become a key factor limiting the overall diffusion rate. Considering that hydrogen has a relatively weak adsorption capacity, but has a high separation coefficient with components such as O2, H2O, CO, and CO2, the present invention specifically fixes the active adsorption material into a honeycomb ordered structure through a resin material, so that its internal diffusion path can be controlled within a range of less than 0.3-0.4mm. When the internal diffusion path is further reduced to less than 0.2mm, the performance of the adsorption material is better, so it is particularly recommended to use this ordered structure adsorption material with an ultra-short internal diffusion path.
[0007] Furthermore, the adsorption material in the dehydration bed is activated alumina, and the specific surface area of the activated alumina is 240-400m 2 / g, pore volume is 0.8-1.5mL / g.
[0008] Furthermore, the O2 adsorption bed is sequentially distributed with cerium molecular sieve adsorbent, Ag, + Modified Li-LSX molecular sieve adsorbent, volume ratio is (2-5):1.
[0009] Furthermore, the adsorption material in the cerium molecular sieve adsorbent is cerium molecular sieve, which is fixed by resin; the preparation method of the cerium molecular sieve is as follows: 4~6gNaY molecular sieve is subjected to ion exchange reaction with 0.15~0.35 mol / LCe2(SO4)3 solution at a temperature of 70-90°C for 3-5h to obtain CeY molecular sieve, which is then placed in ethanol together with 23~27g of trimesic acid after washing and drying, and reacted at 50-80°C for 180~220min, and the cerium molecular sieve is prepared after rinsing and drying.
[0010] Furthermore, the Ag + The adsorbent material in the modified Li-LSX molecular sieve adsorbent is Ag. +Modified Li-LSX molecular sieve, fixed by resin, the Ag + The preparation method of the modified Li-LSX molecular sieve is as follows: add 0.2-0.4 mol / L silver nitrate solution to the aqueous solution of Li-LSX molecular sieve, the mass ratio of Li-LSX molecular sieve to silver nitrate solution is 1:18-22, heat to 60-120°C, react for 70-160 minutes, take out the solid part and dry it in an oven at 110°C for 3-4 hours, heat to 200°C, keep warm for 1-3 hours, heat to 400°C, keep warm for 1-3 hours, and obtain Ag + Modified Li-LSX molecular sieve.
[0011] Furthermore, the CO2 adsorption bed is distributed with modified NaY molecular sieve adsorbent and modified 5A molecular sieve adsorbent in sequence according to the gas flow direction, with a volume ratio of (2-5):1.
[0012] Furthermore, the adsorbent material in the modified NaY molecular sieve adsorbent is a modified NaY molecular sieve, which is fixed by a resin. The preparation method of the modified NaY molecular sieve is as follows: 3-5% sodium aluminate, 1-3% sodium hydroxide, 5.5-7.5% potassium hydroxide, 41.5-43.5% sodium silicate and 44-46% deionized water are mixed to form a uniform gel, and aged at 30-70°C for 3-15h; then crystallized at 95-175°C for 15-48h, filtered and washed to pH <8 after crystallization, and then dried at 120-170°C for 2-12h to obtain the modified NaY molecular sieve, whose specific surface area is 550-950m 2 / g, pore size is 0.6-0.9nm.
[0013] Furthermore, the adsorbent material in the modified 5A molecular sieve adsorbent is a modified 5A molecular sieve, which is fixed by a resin. The preparation method of the modified 5A molecular sieve is as follows: the bar-shaped 5A granular molecular sieve is first dried at 90-120°C for 4 hours, then cooled to 50-70°C and impregnated with hexamethyleneimine for 3-5 hours, the solid part is taken out and allowed to stand at room temperature for 1-1.5 hours, a silica sol aqueous solution with a mass fraction of 22-27% and a calcium hydroxide aqueous solution with a mass fraction of 0.03-0.07% are respectively sprayed uniformly on the impregnated bar-shaped 5A granular molecular sieve, and then ammonia is introduced, followed by drying and calcining at 500-600°C for 2-4 hours to prepare a modified 5A molecular sieve, wherein the number of pores with a pore size less than 10 nm accounts for 30-60% of the total number of pores.
[0014] Furthermore, the CO adsorption bed is sequentially distributed with Cu(I) / 4A molecular sieve adsorbent and 13X molecular sieve adsorbent according to the gas flow direction, with a volume ratio of (2-4):1.
[0015] Furthermore, the adsorbent material in the Cu(I) / 4A molecular sieve adsorbent is Cu(I) / 4A molecular sieve, which is fixed by resin. The preparation method of the Cu(I) / 4A molecular sieve is as follows: 0.1~0.3g of copper nitrate, 45~55g of tetramethylammonium hydroxide, 0.4~0.6g of aluminum hydroxide, 3~5g of aluminum chloride, 3~5g of ethyl orthosilicate and 8~12g of deionized water are mixed, and then crystallization reaction (80~120°C, 180~220min) and sodium borohydride reduction reaction (0.15~0.25g of sodium borohydride, 180~220°C, 180~220min) are carried out in sequence to prepare Cu(I) / 4A molecular sieve.
[0016] Furthermore, the adsorption material in the 13X molecular sieve adsorbent is 13X molecular sieve, which is fixed by resin. The preparation method of the 13X molecular sieve is as follows: 62-66g of tetraethyl orthosilicate, 28-32g of aluminum formate, 18-22g of sodium hydroxide, 1-1.5g of tetrapropylammonium hydroxide and 280-290g of deionized water are mixed, stirred for 1-2h to form a uniform gel, ensuring that the mass ratio of SiO2 / Al2O3 is 2-3, the mass ratio of Na2O / SiO2 is 1-2, aged at room temperature for 3-4h, crystallized at 80-120°C for 10-24h, and dried to prepare a 13X molecular sieve.
[0017] The second aspect of the present invention provides a method for preparing the composite adsorbent described in the first aspect, comprising the following steps: separately preparing a dehydration bed and an adsorbent group.
[0018] The preparation method of the dehydration bed is as follows: activated alumina and aramid fiber are added to polyurethane emulsion (mass fraction is 35-45%) to mix into a uniform slurry, vacuum aged for 18-22 hours, extruded and dried at 95-105°C for 6 hours, and then vacuum activated at 135-145°C for 3-5 hours to obtain a dehydration bed; the mass ratio of the activated alumina, aramid fiber and polyurethane emulsion is 10-20:5-7:4-6.
[0019] The preparation method of the adsorbent group is as follows: the adsorbent material and aramid fiber described in the first aspect are added together into a polyurethane emulsion (mass fraction is 35-45%) to mix into a uniform slurry, vacuum aged for 18-22 hours, extruded and dried at 95-105° C. for 6 hours, and then vacuum activated at 135-145° C. for 3-5 hours to obtain the corresponding adsorbent; the mass ratio of the adsorbent material, aramid fiber and polyurethane emulsion is 10-20:5-7:4-6.
[0020] In the preparation of the adsorbent group, the adsorbent material is the cerium molecular sieve, Ag +Modified Li-LSX molecular sieve, modified NaY molecular sieve, modified 5A molecular sieve, Cu(I) / 4A molecular sieve or 13X molecular sieve, the corresponding adsorbents are cerium molecular sieve adsorbent, Ag + Modified Li-LSX molecular sieve adsorbent, modified NaY molecular sieve adsorbent, modified 5A molecular sieve adsorbent, Cu(I) / 4A molecular sieve adsorbent or 13X molecular sieve adsorbent; according to the direction of gas inflow, the above cerium molecular sieve adsorbent, Ag + Modified Li-LSX molecular sieve adsorbent, modified NaY molecular sieve adsorbent, modified 5A molecular sieve adsorbent, Cu(I) / 4A molecular sieve adsorbent and 13X molecular sieve adsorbent are assembled in sequence to obtain an adsorbent group, and then two dehydration beds are respectively set at both ends of the adsorbent group to obtain the composite adsorbent.
[0021] The above-mentioned composite adsorbent is prepared by extrusion, and the whole extrusion product of the raw powder of the adsorbent material is used as the core component. The advantage is that the extrusion of the raw powder can ensure that the adsorbent material is evenly distributed and tightly stacked. In the study of this preparation method, the present invention focuses on how to achieve flexible adjustment of the diffusion distance and porosity within the composite adsorbent. According to the research of the inventor, the resin material composed of aramid fiber and polyurethane emulsion can be more economical and flexible to carry the above-mentioned adsorbent material. By adjusting the concentration and quality of the resin material such as polyurethane emulsion, the distribution state of the adsorbent material and the internal diffusion distance of the gas can be conveniently adjusted. In the extrusion process, the raw powder of the adsorbent material undergoes melting and molding, and finally shapes a honeycomb composite adsorbent with regular pores and a stable structure. This structure not only ensures the mechanical strength of the adsorbent, but also gives it a large specific surface area and a developed pore structure, thereby providing sufficient adsorption capacity.
[0022] In addition, the whole extrusion process of raw powder also makes the preparation of composite adsorbents simpler and more efficient. Compared with the preparation method of traditional granular adsorbents, the whole extrusion process can reduce the gaps and friction between adsorbent particles, thereby reducing the energy loss during gas flow.
[0023] The third aspect of the present invention provides application of the composite adsorbent described in the first aspect in the field of hydrogen recovery.
[0024] In the above applications, the hydrogen mainly refers to hydrogen-rich tail gas, in which hydrogen accounts for more than 40% of the volume, and also includes impurity gases, such as mixed gases including O2, H2O, CO, CO2, which mainly come from chemical, petroleum or metallurgical industries, such as chlor-alkali tail gas, coke oven gas or liquefied natural gas hydrogen-rich tail gas.
[0025] The composite adsorbent can be applied to pressure swing adsorption or rapid pressure swing adsorption technology, and a common application method in the field is to be applied to an adsorption tower or an adsorption tank.
[0026] According to a fourth aspect of the present invention, there is provided a tail gas adsorption tower, in which the composite adsorbent according to the first aspect is arranged.
[0027] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention provides a composite adsorbent, in which a dehydration bed, an O2 adsorption bed, a CO2 adsorption bed, a CO adsorption bed and a dehydration bed are sequentially distributed from the direction of gas inlet to outlet, and the adsorbent material is melted in a resin material and then extruded and shaped, so that the adsorbent material satisfies a certain distribution law. According to the preparation method provided by the present invention, the composite adsorbent is honeycomb-shaped, the gas diffusion distance is 0.1~0.3mm, and the internal porosity of the adsorbent is 50~70%. The above configuration not only has good adsorption performance for impurities such as O2, H2O, CO, CO2 in hydrogen-rich tail gas, but also the composite adsorbent adopts a laminated structure, which not only improves the specific surface area and pore structure stability of the adsorbent, but also enhances the selectivity for hydrogen, so that hydrogen can be separated from hydrogen-rich tail gas more efficiently.
[0028] 2. The composite adsorbent provided by the present invention is prepared by extrusion. Compared with the granules that require granulation, the process of the present invention is simpler, and the gas internal diffusion path and the porosity of the composite adsorbent can be adjusted by adjusting the dosage of the adsorbent material and the concentration of the polyurethane emulsion. Increasing the concentration of the polyurethane emulsion and reducing the mass ratio are conducive to obtaining a shorter internal diffusion path and increasing the porosity. In addition, aramid fiber and polyurethane emulsion are both common commercial products, and the cost is more economical. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0030] Figure 1 This is a schematic diagram of the structure of the tail gas adsorption tower described in Example 4; Among them, 1 is a dehydration bed; 2 is a 13X molecular sieve adsorbent; 3 is a Cu(I) / 4A molecular sieve adsorbent; 4 is a modified 5A molecular sieve adsorbent; 5 is a modified NaY molecular sieve adsorbent; 6 is an Ag + Modified Li-LSX molecular sieve adsorbent; 7 is a cerium molecular sieve adsorbent. DETAILED DESCRIPTION
[0031] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0032] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0033] As introduced in the background technology, the pressure swing adsorption method applied to hydrogen recovery from hydrogen-rich tail gas has the advantages of flexible operation and low energy consumption. However, the existing adsorbents still have problems such as limited adsorption capacity, low selectivity, and poor regeneration performance. In view of the above problems existing in the prior art, the present invention provides a honeycomb adsorbent with regular pores, which controls the internal diffusion path within the range of less than 0.3-0.4mm, fully utilizes the characteristic differences between hydrogen and other components, and brings innovative solutions to the field of hydrogen purification technology.
[0034] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0035] Example 1 In this embodiment, a composite adsorbent is provided, wherein the two ends of the composite adsorbent are dehydration beds, and the middle part is composed of two adsorption bed groups tightly connected end to end. In each adsorption bed group, O2 adsorption bed, CO2 adsorption bed, and CO adsorption bed are distributed in sequence from the direction of gas inlet to outlet; compared with the total volume of the composite adsorbent, the dehydration beds at the two ends account for 35% of the total volume, the O2 adsorption bed accounts for 35% of the volume, the CO2 adsorption bed accounts for 15% of the volume, and the CO adsorption bed accounts for 15% of the volume. The overall internal diffusion distance of the composite adsorbent is 0.2 mm, and the porosity is 60%.
[0036] The preparation process of the composite adsorbent comprises the following steps: 1. Dehydration bed: The adsorption component is activated alumina, and the specific surface area of the activated alumina is 280m 2 / g, pore volume 1mL / g, the volume ratio of the two dehydration beds distributed at both ends of the composite adsorbent is 1:1. The preparation method of the dehydration bed is as follows: Activated alumina, aramid fiber, and polyurethane emulsion (mass fraction of 40%) are mixed in a mass ratio of 15:6:5, and water is added to the above mixture at the rate of 1000g of the mixture corresponding to 1L of water. The mixture is dispersed by a disperser to form a uniform mixed slurry. The slurry is aged in a vacuum mud refiner for 20 hours, and then extruded in a hydraulic extruder. The extruded sample is dried at 100°C for 6 hours, and a dehydration bed is obtained after vacuum activation at 140°C for 4 hours.
[0037] 2. O2 adsorption bed: Ce molecular sieve adsorbent and Ag are distributed in sequence according to the gas flow direction. + Modified Li-LSX molecular sieve adsorbent, volume ratio is 2:1, preparation process is as follows: (1) Preparation of cerium molecular sieve: 5 g of NaY molecular sieve was subjected to ion exchange reaction with 100 mL of 0.2 mol / L Ce2(SO4)3 solution at 80°C for 4 h to obtain CeY molecular sieve. The CeY molecular sieve was washed and dried, and then placed in 200 mL of ethanol with 25 g of trimesic acid, and reacted at 70°C for 200 min. The cerium molecular sieve was obtained after rinsing and drying. (2) Ag + Preparation of modified Li-LSX molecular sieve: 0.3 mol / L silver nitrate solution was added to the aqueous solution of Li-LSX molecular sieve, the mass ratio of Li-LSX molecular sieve to silver nitrate solution was 1:20, the temperature was raised to 100°C for reaction for 100 minutes, the solid part was separated and retained and placed in an oven at 110°C for drying for 3 hours, the temperature was raised to 200°C for 2 hours, and the temperature was raised to 400°C for 2 hours to obtain the Ag + Modified Li-LSX molecular sieve.
[0038] (3) Ce molecular sieve or Ag + Modified Li-LSX molecular sieve, aramid fiber, and polyurethane emulsion (mass fraction of 40%) were mixed in a mass ratio of 15:6:5; water was added to the above mixture according to 1000g of the mixture corresponding to 1L of water, and then dispersed by a disperser to form a uniform mixed slurry; the mixture was placed in a vacuum mud refiner for aging for 20 hours, and then extruded in a hydraulic extruder, and the extruded sample was dried at 100°C for 6 hours, and after vacuum activation at 140°C for 4 hours, a cerium molecular sieve adsorbent and Ag were formed. + Modified Li-LSX molecular sieve adsorbent was assembled in sequence.
[0039] 3. CO2 adsorption bed: Modified NaY molecular sieve adsorbent and modified 5A molecular sieve adsorbent are distributed in sequence according to the gas flow direction, with a volume ratio of 2:1. The preparation process is as follows: (1) Preparation of modified NaY molecular sieve: Sodium aluminate, sodium hydroxide, potassium hydroxide, sodium silicate and deionized water were mixed in the mass percentages of 4%, 2%, 6.5%, 42.5% and 45% to form a uniform gel, which was aged at 40°C for 13 h and crystallized at 150°C for 24 h. After crystallization, the gel was filtered and washed until the pH value was less than 8, and then dried at 120°C for 12 h to prepare a modified NaY molecular sieve with a specific surface area of 950 m 2 / g, pore size is 0.9 nm; (2) Preparation of modified 5A molecular sieve: The bar-shaped 5A granular molecular sieve was first dried at 100°C for 4 hours, then cooled to 60°C and impregnated with hexamethyleneimine liquid for 4 hours. The mass ratio of the above-mentioned bar-shaped 5A granular molecular sieve to the hexamethyleneimine liquid was 5:4. 200 g of the impregnated bar-shaped 5A granular molecular sieve was taken out and allowed to stand at room temperature for 1 hour. 20 g of a 25% silica sol aqueous solution and 10 g of a 0.05% calcium hydroxide aqueous solution were sprayed on the impregnated bar-shaped 5A granular molecular sieve, ammonia gas was introduced, and then dried and calcined at 550°C for 3 hours to prepare a modified 5A molecular sieve in which the number of pores with a pore size less than 10 nm accounted for 50% of the total number of pores.
[0040] (3) Modified NaY molecular sieve or modified 5A molecular sieve, aramid fiber, and polyurethane emulsion (mass fraction of 40%) were mixed in a mass ratio of 15:6:5, and water was added to the above mixture at a rate of 1000 g of the mixture corresponding to 1 L of water. The mixture was dispersed by a disperser to form a uniform mixed slurry. The mixture was placed in a vacuum mud refiner for aging for 20 h, and then placed in a hydraulic extruder for extrusion. The extruded sample was dried at 100°C for 6 h, and vacuum activated at 140°C for 4 h to obtain modified NaY molecular sieve and modified 5A molecular sieve, which were assembled in sequence.
[0041] 4. CO adsorption bed: Cu(I) / 4A molecular sieve adsorbent and 13X molecular sieve adsorbent are distributed in sequence according to the gas flow direction, with a volume ratio of 2:1. The preparation process is as follows: (1) Preparation of Cu(I) / 4A molecular sieve: Copper nitrate (0.2 g), tetramethylammonium hydroxide (50 g), aluminum hydroxide (0.5 g), aluminum chloride (4 g), tetraethyl orthosilicate (4 g) and deionized water (10 g) were mixed, and then crystallized (100 °C, 200 min) and reduced with sodium borohydride (0.15 g sodium borohydride was added and reacted at 200 °C for 200 min) to prepare Cu(I) / 4A molecular sieve; (2) Preparation of 13X molecular sieve: Mix ethyl orthosilicate (64 g), aluminum formate (30.97 g), sodium hydroxide (20.43 g), tetrapropylammonium hydroxide (1.34 g), and deionized water (283.33 g), and stir for 1 h to form a uniform gel, ensuring that the mass ratio of SiO2 / Al2O3 is 2-3 and the mass ratio of Na2O / SiO2 is 1-2. Age at room temperature for 4 h, crystallize at 100°C for 18 h, and then dry to prepare 13X molecular sieve.
[0042] (3) Cu(I) / 4A molecular sieve or 13X molecular sieve, aramid fiber, and polyurethane emulsion (mass fraction of 40%) were mixed in a mass ratio of 15:6:5; water was added to the above mixture according to the ratio of 1000g of the mixture to 1L of water, and then dispersed by a disperser to form a uniform mixed slurry; the mixture was placed in a vacuum mud refiner for aging for 20h, and then extruded in a hydraulic extruder. The extruded sample was dried at 100℃ for 6h, and vacuum activated at 140℃ for 4h to form Cu(I) / 4A molecular sieve adsorbent and 13X molecular sieve adsorbent, which were assembled in sequence.
[0043] According to the flow direction of the gas to be treated, the dehydration bed and the adsorption beds are installed in sequence and tightly connected.
[0044] Example 2 In this embodiment, another composite adsorbent is provided, wherein the two ends of the composite adsorbent are dehydration beds, and the middle part is composed of two adsorption bed groups connected closely end to end. In each adsorption bed group, O2 adsorption bed, CO2 adsorption bed, and CO adsorption bed are distributed in sequence from the direction of gas inlet to outlet; compared with the total volume of the composite adsorbent: the dehydration beds at the two ends account for 30% of the total volume, the O2 adsorption bed accounts for 30% of the volume, the CO2 adsorption bed accounts for 20% of the volume, and the CO adsorption bed accounts for 20% of the volume. The overall internal diffusion distance of the composite adsorbent is 0.3mm, and the porosity is 50%.
[0045] The preparation process of the composite adsorbent comprises the following steps: 1. Dehydration bed: The adsorption component is activated alumina, and the specific surface area of the activated alumina is 240m 2 / g, pore volume 0.8mL / g, the volume ratio of the two dehydration beds distributed at both ends of the composite adsorbent is 1:1. The preparation method of the dehydration bed is as follows: Activated alumina, aramid fiber, and polyurethane emulsion (mass fraction of 35%) were mixed in a mass ratio of 10:5:4, and water was added to the above mixture at the rate of 1000g of the mixture corresponding to 1L of water. The mixture was dispersed by a disperser to form a uniform mixed slurry. The slurry was aged in a vacuum mud refiner for 18 hours, and then extruded in a hydraulic extruder. The extruded sample was dried at 95°C for 6 hours, and a dehydration bed was obtained after vacuum activation at 135°C for 5 hours.
[0046] 2. O2 adsorption bed: Ce molecular sieve adsorbent and Ag are distributed in sequence according to the gas flow direction. + Modified Li-LSX molecular sieve adsorbent, volume ratio is 2:1, preparation process is as follows: (1) Preparation of cerium molecular sieve: 4 g of NaY molecular sieve was subjected to ion exchange reaction with 100 mL of 0.15 mol / L Ce2(SO4)3 solution at 90°C for 5 h to obtain CeY molecular sieve. The CeY molecular sieve and 23 g of trimesic acid were placed in 200 mL of ethanol and reacted at 50°C for 220 min. The cerium molecular sieve was obtained after rinsing and drying. (2) Ag + Preparation of modified Li-LSX molecular sieve: 0.2 mol / L silver nitrate solution was added to the aqueous solution of Li-LSX molecular sieve, the mass ratio of Li-LSX molecular sieve to silver nitrate solution was 1:18, the temperature was raised to 60°C for reaction for 160 minutes, the solid part was separated and retained, placed in an oven at 110°C for drying for 4 hours, the temperature was raised to 200°C for 3 hours, and then the temperature was raised to 400°C for 1 hour to obtain the Ag + Modified Li-LSX molecular sieve.
[0047] (3) Ce molecular sieve or Ag + The modified Li-LSX molecular sieve, aramid fiber, and polyurethane emulsion (mass fraction of 35%) were mixed in a mass ratio of 10:5:4, and water was added to the above mixture according to 1000g of the mixture corresponding to 1L of water. The mixture was dispersed by a disperser to form a uniform mixed slurry; the mixture was placed in a vacuum mud refiner for aging for 18 hours, and then extruded in a hydraulic extruder. The extruded sample was dried at 95°C for 6 hours, and then vacuum activated at 135°C for 5 hours to form a cerium molecular sieve adsorbent and Ag. + Modified Li-LSX molecular sieve adsorbent was assembled in sequence.
[0048] 3. CO2 adsorption bed: Modified NaY molecular sieve adsorbent and modified 5A molecular sieve adsorbent are distributed in sequence according to the gas flow direction, with a volume ratio of 2:1. The preparation process is as follows: (1) Preparation of modified NaY molecular sieve: Sodium aluminate, sodium hydroxide, potassium hydroxide, sodium silicate and deionized water were mixed in the order of 3%, 1%, 7.5%, 43.5% and 45% by mass, and the mixture was aged at 30°C for 15 h and crystallized at 175°C for 15 h. After crystallization, the mixture was filtered and washed to prepare a modified NaY molecular sieve with a specific surface area of 950 m 2 / g, pore size is 0.9 nm; (2) Preparation of modified 5A molecular sieve: The bar-shaped 5A granular molecular sieve was first dried at 90°C for 4 hours, then cooled to 50°C and impregnated with hexamethyleneimine liquid for 3 hours. The mass ratio of the above-mentioned bar-shaped 5A granular molecular sieve to the hexamethyleneimine liquid was 5:4. 200 g of the impregnated bar-shaped 5A granular molecular sieve was taken out and allowed to stand at room temperature for 1.5 hours. 20 g of a 22% silica sol aqueous solution and 10 g of a 0.03% calcium hydroxide aqueous solution were sprayed on the impregnated bar-shaped 5A granular molecular sieve, ammonia gas was introduced, and then dried and calcined at 500°C for 4 hours to prepare a modified 5A molecular sieve in which the number of pores with a pore size of less than 10 nm accounted for 60% of the total number of pores.
[0049] (3) Modified NaY molecular sieve or modified 5A molecular sieve, aramid fiber, and polyurethane emulsion (mass fraction of 35%) were mixed in a mass ratio of 10:5:4, and water was added to the above mixture at a rate of 1000 g of the mixture corresponding to 1 L of water. The mixture was dispersed by a disperser to form a uniform mixed slurry. The mixture was placed in a vacuum mud refiner for aging for 18 h, and then placed in a hydraulic extruder for extrusion. The extruded sample was dried at 95°C for 6 h, and then vacuum activated at 135°C for 5 h to form modified NaY molecular sieve and modified 5A molecular sieve, which were assembled in sequence.
[0050] 4. CO adsorption bed: Cu(I) / 4A molecular sieve adsorbent and 13X molecular sieve adsorbent are distributed in sequence according to the gas flow direction, with a volume ratio of 4:1. The preparation process is as follows: (1) Preparation of Cu(I) / 4A molecular sieve: Copper nitrate (0.1 g), tetramethylammonium hydroxide (45 g), aluminum hydroxide (0.4 g), aluminum chloride (3 g), tetraethyl orthosilicate (3 g) and deionized water (8 g) were mixed, and then crystallized (80°C, 220 min) and reduced with sodium borohydride (0.15 g sodium borohydride was added and reacted at 180°C for 180 min) to prepare Cu(I) / 4A molecular sieve; (2) Preparation of 13X molecular sieve: Mix ethyl orthosilicate (62 g), aluminum formate (28 g), sodium hydroxide (18 g), tetrapropylammonium hydroxide (1.00 g), and deionized water (280 g), and stir for 1 h to form a uniform gel, ensuring that the mass ratio of SiO2 / Al2O3 is 2-3 and the mass ratio of Na2O / SiO2 is 1-2. Age at room temperature for 4 h, crystallize at 80°C for 24 h, and then dry to prepare 13X molecular sieve.
[0051] (3) Cu(I) / 4A molecular sieve or 13X molecular sieve, aramid fiber, and polyurethane emulsion (mass fraction of 35%) were mixed in a mass ratio of 10:5:4, and water was added to the above mixture at a rate of 1000 g of the mixture corresponding to 1 L of water. The mixture was dispersed by a disperser to form a uniform mixed slurry. The mixture was placed in a vacuum mud refiner for aging for 18 h, and then extruded in a hydraulic extruder. The extruded sample was dried at 95°C for 6 h, and vacuum activated at 135°C for 5 h to form Cu(I) / 4A molecular sieve adsorbent and 13X molecular sieve adsorbent, which were assembled in sequence.
[0052] According to the flow direction of the gas to be treated, the dehydration bed and the adsorption beds are installed in sequence and tightly connected.
[0053] Example 3 In this embodiment, another composite adsorbent is provided, wherein the two ends of the composite adsorbent are dehydration beds, and the middle part is composed of two adsorption bed groups connected closely end to end. In each adsorption bed group, O2 adsorption bed, CO2 adsorption bed, and CO adsorption bed are distributed in sequence from the direction of gas inlet to outlet; compared with the total volume of the composite adsorbent: the dehydration beds at the two ends account for 40% of the total volume, the O2 adsorption bed accounts for 40% of the volume, the CO2 adsorption bed accounts for 10% of the volume, and the CO adsorption bed accounts for 10% of the volume. The overall internal diffusion distance of the composite adsorbent is 0.1mm, and the porosity is 70%.
[0054] The preparation process of the composite adsorbent comprises the following steps: 1. Dehydration bed: The adsorption component is activated alumina, and the specific surface area of the activated alumina is 400m 2 / g, pore volume 1.5mL / g, the volume ratio of the two dehydration beds distributed at both ends of the composite adsorbent is 1:1. The preparation method of the dehydration bed is as follows: Activated alumina, aramid fiber, and polyurethane emulsion (mass fraction of 45%) are mixed in a mass ratio of 20:7:6, and water is added to the above mixture at the rate of 1000g of the mixture corresponding to 1L of water. The mixture is dispersed by a disperser to form a uniform mixed slurry. The slurry is aged in a vacuum mud refiner for 22 hours, and then extruded in a hydraulic extruder. The extruded sample is dried at 105°C for 6 hours, and a dehydration bed is obtained after vacuum activation at 145°C for 3 hours.
[0055] 2. O2 adsorption bed: Ce molecular sieve adsorbent and Ag are distributed in sequence according to the gas flow direction. + Modified Li-LSX molecular sieve adsorbent, volume ratio is 2:1, preparation process is as follows: (1) Preparation of cerium molecular sieve: 6 g of NaY molecular sieve was subjected to ion exchange reaction with 100 mL of 0.35 mol / L Ce2(SO4)3 solution at 70°C for 3 h to obtain CeY molecular sieve. The CeY molecular sieve and 27 g of trimesic acid were placed in 200 mL of ethanol and reacted at 80°C for 180 min. The cerium molecular sieve was obtained after rinsing and drying. (2) Ag + Preparation of modified Li-LSX molecular sieve: 0.4 mol / L silver nitrate solution was added to the aqueous solution of Li-LSX molecular sieve, the mass ratio of Li-LSX molecular sieve to silver nitrate solution was 1:22, the temperature was raised to 120°C for reaction for 70 minutes, the solid part was separated and retained, placed in an oven at 110°C for drying for 4 hours, the temperature was raised to 200°C for 1 hour, and then the temperature was raised to 400°C for 3 hours to obtain the Ag + Modified Li-LSX molecular sieve.
[0056] (3) Ce molecular sieve or Ag + The modified Li-LSX molecular sieve, aramid fiber, and polyurethane emulsion (mass fraction of 45%) were mixed in a mass ratio of 20:7:6, and water was added to the above mixture according to 1000g of the mixture corresponding to 1L of water. The mixture was dispersed by a disperser to form a uniform mixed slurry; the mixture was placed in a vacuum mud refiner for aging for 22 hours, and then extruded in a hydraulic extruder. The extruded sample was dried at 105°C for 6 hours, and then vacuum activated at 145°C for 3 hours to form a cerium molecular sieve adsorbent and Ag. + Modified Li-LSX molecular sieve adsorbent was assembled in sequence.
[0057] 3. CO2 adsorption bed: Modified NaY molecular sieve adsorbent and modified 5A molecular sieve adsorbent are distributed in sequence according to the gas flow direction, with a volume ratio of 5:1. The preparation process is as follows: (1) Preparation of modified NaY molecular sieve: Sodium aluminate, sodium hydroxide, potassium hydroxide, sodium silicate and deionized water were mixed in the order of 5%, 3%, 5.5%, 41.5% and 45% by mass, and the mixture was aged at 70°C for 3 hours, crystallized at 95°C for 48 hours, filtered and washed to pH <8 after crystallization, and then dried at 170°C for 2 hours to obtain the modified NaY molecular sieve with a specific surface area of 550 m 2 / g, pore size is 0.6nm; (2) Preparation of modified 5A molecular sieve: The bar-shaped 5A granular molecular sieve was first dried at 120°C for 4 hours, then cooled to 70°C and impregnated with hexamethyleneimine liquid for 5 hours. The mass ratio of the above-mentioned bar-shaped 5A granular molecular sieve to the hexamethyleneimine liquid was 5:4. 200 g of the impregnated bar-shaped 5A granular molecular sieve was taken out and allowed to stand at room temperature for 1 hour. 20 g of a 27% silica sol aqueous solution and 10 g of a 0.07% calcium hydroxide aqueous solution were sprayed on the impregnated bar-shaped 5A granular molecular sieve, ammonia gas was introduced, and then dried and calcined at 600°C for 2 hours to prepare a modified 5A molecular sieve in which the number of pores with a pore size less than 10 nm accounted for 30% of the total number of pores.
[0058] (3) Modified NaY molecular sieve or modified 5A molecular sieve, aramid fiber, and polyurethane emulsion (mass fraction of 45%) were mixed in a mass ratio of 20:7:6, and water was added to the above mixture at a rate of 1000 g of the mixture corresponding to 1 L of water. The mixture was dispersed by a disperser to form a uniform mixed slurry. The mixture was placed in a vacuum mud refiner for aging for 22 h, and then placed in a hydraulic extruder for extrusion. The extruded sample was dried at 105°C for 6 h, and after vacuum activation at 145°C for 3 h, the modified NaY molecular sieve and the modified 5A molecular sieve were assembled in sequence.
[0059] 4. CO adsorption bed: Cu(I) / 4A molecular sieve adsorbent and 13X molecular sieve adsorbent are distributed in sequence according to the gas flow direction, with a volume ratio of 4:1. The preparation process is as follows: (1) Preparation of Cu(I) / 4A molecular sieve: Copper nitrate (0.3 g), tetramethylammonium hydroxide (55 g), aluminum hydroxide (0.6 g), aluminum chloride (5 g), tetraethyl orthosilicate (5 g) and deionized water (12 g) were mixed, and then crystallized (120 °C, 180 min) and reduced with sodium borohydride (0.25 g sodium borohydride was added and reacted at 220 °C for 220 min) to prepare Cu(I) / 4A molecular sieve; (2) Preparation of 13X molecular sieve: Mix ethyl orthosilicate (66 g), aluminum formate (32 g), sodium hydroxide (22 g), tetrapropylammonium hydroxide (1.50 g), and deionized water (290 g), and stir for 2 h to form a uniform gel, ensuring that the mass ratio of SiO2 / Al2O3 is 2-3 and the mass ratio of Na2O / SiO2 is 1-2. Age at room temperature for 3 h, crystallize at 120°C for 10 h, and then dry to prepare 13X molecular sieve.
[0060] (3) Cu(I) / 4A molecular sieve or 13X molecular sieve, aramid fiber, and polyurethane emulsion (mass fraction of 45%) were mixed in a mass ratio of 20:7:6, and water was added to the above mixture at a rate of 1000g of the mixture corresponding to 1L of water. The mixture was dispersed by a disperser to form a uniform mixed slurry. The mixture was placed in a vacuum mud refiner for aging for 22 hours, and then extruded in a hydraulic extruder. The extruded sample was dried at 105°C for 6 hours. After vacuum activation at 145°C for 3 hours, the Cu(I) / 4A molecular sieve adsorbent and the 13X molecular sieve adsorbent were assembled in sequence.
[0061] According to the flow direction of the gas to be treated, the dehydration bed and the adsorption beds are installed in sequence and tightly connected.
[0062] Example 4 In this embodiment, a tail gas adsorption tower is provided, in which the composite adsorbent in Example 1 is arranged. The structural schematic diagram of the tail gas adsorption tower and the composite adsorbent is as shown in FIG. Figure 1 As shown, the two ends are dehydration beds 1, and the middle part is composed of two adsorption bed groups connected closely end to end. In each adsorption bed group, O2 adsorption bed, CO2 adsorption bed, and CO adsorption bed are distributed in sequence according to the direction of gas inflow to outflow. Specifically, according to the direction of gas inflow during adsorption, the structure of the composite adsorbent is as follows: dehydration bed 1, cerium molecular sieve adsorbent 7, Ag + Modified Li-LSX molecular sieve adsorbent 6, modified NaY molecular sieve adsorbent 5, modified 5A molecular sieve adsorbent 4, Cu(I) / 4A molecular sieve adsorbent 3, 13X molecular sieve adsorbent 2, cerium molecular sieve adsorbent 7, Ag + Modified Li-LSX molecular sieve adsorbent 6, modified NaY molecular sieve adsorbent 5, modified 5A molecular sieve adsorbent 4, Cu(I) / 4A molecular sieve adsorbent 3, 13X type molecular sieve adsorbent 2, dehydration bed 1.
[0063] The process of using the above tail gas adsorption tower for hydrogen-rich tail gas adsorption is as follows: the tail gas to be treated is introduced from the bottom of the tail gas adsorption tower, and the treated hydrogen is removed from the top of the tail gas adsorption tower. The temperature in the tail gas adsorption tower is 10°C to 30°C, and the pressure condition is 2.5-2.8 MPa.
[0064] The process of using the above-mentioned tail gas adsorption tower for desorption of impurity gases is as follows: close the top of the tail gas adsorption tower, increase the temperature in the tail gas adsorption tower to 60°C~80°C, and reduce the pressure to -0.2~0.1MPa.
[0065] Performance Testing 1. Impurity gas adsorption performance In this embodiment, the hydrogen-containing tail gas of the chlor-alkali industry is taken as the test object, and the performance of the composite adsorbent in the above embodiment is measured. O2, H2O, CO, and CO2 are taken as the main impurity gases to be separated. It is measured that the contents of O2, H2O, CO, and CO2 in the hydrogen-containing tail gas to be adsorbed are 400 ppm, 300 ppm, 50 ppm, and 30 ppm, respectively.
[0066] The control group is a granular adsorbent, and the preparation method is as follows: the activated alumina, cerium molecular sieve, Ag in Example 1 are added to the granular adsorbent. + Modified Li-LSX molecular sieve, modified NaY molecular sieve, modified 5A molecular sieve, Cu(I) / 4A molecular sieve, 13X molecular sieve aramid fiber, and polyurethane emulsion (mass fraction of 40%) are mixed in a mass ratio of 15:6:5, and water is added to the above mixture according to 1000g of the mixture corresponding to 1L of water. The mixture is dispersed by a disperser to form a uniform mixed slurry. The mixed slurry is granulated by a fluidized bed to obtain granules with a size of 3mm x 3mm x 1mm and a surface area of ≥600m 2 / g, and compress and pack the above-mentioned granular adsorbent in the same order as in Example 1 so that the volume proportion of each part is the same as in Example 1.
[0067] The above hydrogen-containing tail gas was introduced into Example 1 and the control group respectively, and the process conditions in Example 4 were used to carry out hydrogen-containing tail gas adsorption and impurity gas desorption. When the hydrogen-containing tail gas was adsorbed, the adsorbed tail gas was collected from the top of the tower and the impurity content therein was detected. The results are shown in Table 1 below: Table 1 Adsorption effect of composite adsorbent on hydrogen-containing tail gas in the examples and control group According to the results in Table 1, the content of impurity gases in the hydrogen-containing tail gas treated with the composite adsorbent in Example 1 is significantly reduced, and is lower in Example 1 than in the control group, which means that the composite adsorbent provided by the present invention is used to adsorb impurity gases and purify hydrogen more thoroughly. The composite adsorbents in the control group and Example 1 have the same adsorption material and the same resin fixing material. The main difference is that the different preparation methods lead to different distribution characteristics of the adsorption material. The honeycomb distribution method provided in the present application is more conducive to the rapid penetration of hydrogen, thereby achieving separation from other impurity gases.
[0068] The effects of Examples 1-3 are basically similar, and all can achieve effective removal of impurity gases. The purity of the recovered hydrogen can reach more than 98%, which significantly exceeds the adsorption level of more than 90% of existing hydrogen adsorbents.
[0069] In addition, research has found that the desorption effect of the composite adsorbent provided by the present invention is also better than that of the granular adsorbent. Under the same desorption temperature and pressure conditions, the service life of the composite adsorbent of the present invention is extended by more than 60% compared with the granular adsorbent.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A composite adsorbent, characterized in that: The composite adsorbent has dehydration beds at both ends, and is composed of at least one adsorbent group connected end to end in sequence in the middle. Each adsorbent group is distributed with O2 adsorption beds, CO2 adsorption beds and CO adsorption beds in sequence from the direction of gas inlet to outlet. Compared with the total volume of the composite adsorbent, the dehydration beds at both ends account for 30-40% of the total volume, the O2 adsorption bed accounts for 30-40% of the volume, the CO2 adsorption bed accounts for 10-20% of the volume, and the CO adsorption bed accounts for 10-20% of the volume. The composite adsorbent is honeycomb-shaped, with an internal diffusion distance of 0.1-0.3 mm and a porosity of 50-70%. The adsorption material in the dehydration bed is activated alumina with a specific surface area of 240-400m 2 / g, pore volume is 0.8-1.5mL / g; The O2 adsorption bed is sequentially distributed with cerium molecular sieve adsorbent, Ag, + Modified Li-LSX molecular sieve adsorbent, volume ratio is (2-5):1; The CO2 adsorption bed is sequentially distributed with modified NaY molecular sieve adsorbent and modified 5A molecular sieve adsorbent according to the gas flow direction, with a volume ratio of (2-5):1; The CO adsorption bed is distributed with Cu(I) / 4A molecular sieve adsorbent and 13X molecular sieve adsorbent in sequence according to the gas flow direction, with a volume ratio of (2-4):
1.
2. The composite adsorbent according to claim 1, characterized in that: The adsorbent material in the cerium molecular sieve adsorbent is a cerium molecular sieve fixed by a resin; The preparation method of the cerium molecular sieve is as follows: 4-6g NaY molecular sieve is subjected to ion exchange reaction with 0.15-0.35 mol / LCe2(SO4)3 solution at a temperature of 70-90°C for 3-5h to obtain CeY molecular sieve, which is then placed in ethanol together with 23-27g trimesic acid after washing and drying, and reacted at 50-80°C for 180-220min, and then rinsed and dried to prepare the cerium molecular sieve; The Ag + The adsorbent material in the modified Li-LSX molecular sieve adsorbent is Ag. + Modified Li-LSX molecular sieve, fixed by resin, the Ag + The preparation method of the modified Li-LSX molecular sieve is as follows: add 0.2-0.4 mol / L silver nitrate solution to the aqueous solution of Li-LSX molecular sieve, the mass ratio of Li-LSX molecular sieve to silver nitrate solution is 1:18-22, heat to 60-120°C, react for 70-160 minutes, take out the solid part and dry it in an oven at 110°C for 3-4 hours, heat to 200°C, keep warm for 1-3 hours, heat to 400°C, keep warm for 1-3 hours, and obtain Ag + Modified Li-LSX molecular sieve.
3. The composite adsorbent according to claim 1, characterized in that: The adsorbent material in the modified NaY molecular sieve adsorbent is a modified NaY molecular sieve fixed by a resin; The preparation method of the modified NaY molecular sieve is as follows: 3-5% sodium aluminate, 1-3% sodium hydroxide, 5.5-7.5% potassium hydroxide, 41.5-43.5% sodium silicate and 44-46% deionized water are mixed to form a uniform gel, and the gel is aged at 30-70°C for 3-15h; then the gel is crystallized at 95-175°C for 15-48h, filtered and washed to a pH value less than 8 after crystallization, and then dried at 120-170°C for 2-12h to obtain the modified NaY molecular sieve, whose specific surface area is 550-950m 2 / g, pore size is 0.6-0.9nm; The adsorbent material in the modified 5A molecular sieve adsorbent is a modified 5A molecular sieve fixed by a resin. The preparation method of the modified 5A molecular sieve is as follows: a strip-shaped 5A granular molecular sieve is first dried at 90-120°C for 4 hours, then cooled to 50-70°C and impregnated with hexamethyleneimine for 3-5 hours, the solid part is taken out and allowed to stand at room temperature for 1-1.5 hours, a silica sol aqueous solution with a mass fraction of 22-27% and a calcium hydroxide aqueous solution with a mass fraction of 0.03-0.07% are respectively evenly sprayed on the impregnated strip-shaped 5A granular molecular sieve, ammonia is introduced, and then the modified 5A molecular sieve is dried and calcined at 500-600°C for 2-4 hours to prepare a modified 5A molecular sieve, wherein the number of pores with a pore size less than 10 nm accounts for 30-60% of the total number of pores.
4. The composite adsorbent according to claim 1, characterized in that: The adsorbent material in the Cu(I) / 4A molecular sieve adsorbent is Cu(I) / 4A molecular sieve, which is fixed by resin. The preparation method of the Cu(I) / 4A molecular sieve is as follows: 0.1-0.3g of copper nitrate, 45-55g of tetramethylammonium hydroxide, 0.4-0.6g of aluminum hydroxide, 3-5g of aluminum chloride, 3-5g of ethyl orthosilicate and 8-12g of deionized water are mixed, and then crystallization reaction and sodium borohydride reduction reaction are carried out in sequence to prepare the Cu(I) / 4A molecular sieve; the crystallization reaction temperature is 80-120°C, the reaction time is 180-220min, and the sodium borohydride reduction reaction conditions are as follows: 0.15-0.25g of sodium borohydride is added and reacted at 180-220°C for 180-220min. The adsorption material in the 13X molecular sieve adsorbent is 13X molecular sieve, which is fixed by resin. The preparation method of the 13X molecular sieve is as follows: 62-66g of tetraethyl orthosilicate, 28-32g of aluminum formate, 18-22g of sodium hydroxide, 1-1.5g of tetrapropylammonium hydroxide and 280-290g of deionized water are mixed, stirred for 1-2h to form a uniform gel, ensuring that the mass ratio of SiO2 / Al2O3 is 2-3, the mass ratio of Na2O / SiO2 is 1-2, aged at room temperature for 3-4h, crystallized at 80-120°C for 10-24h, and dried to prepare a 13X molecular sieve.
5. The method for preparing the composite adsorbent according to any one of claims 1 to 4, characterized in that: The invention comprises preparing a dehydration bed and an adsorbent group respectively; wherein the preparation method of the dehydration bed is as follows: the activated alumina and aramid fiber described in claim 1 are added together with a polyurethane emulsion with a mass fraction of 35-45% to mix into a uniform slurry, vacuum aged for 18-22 hours, extruded and dried at 95-105° C. for 6 hours, and then vacuum activated at 135-145° C. for 3-5 hours to obtain a dehydration bed; the mass ratio of the activated alumina, aramid fiber and polyurethane emulsion is 10-20:5-7:4-6; The preparation method of the adsorbent group is as follows: the adsorbent material and aramid fiber are added together to a polyurethane emulsion with a mass fraction of 35-45% to form a uniform slurry, vacuum aged for 18-22 hours, extruded and dried at 95-105° C. for 6 hours, and then vacuum activated at 135-145° C. for 3-5 hours to obtain the corresponding adsorbent; the mass ratio of the adsorbent material, aramid fiber and polyurethane emulsion is 10-20:5-7:4-6; the adsorbent material is the cerium molecular sieve or Ag described in claim 2 + Modified Li-LSX molecular sieve, modified NaY molecular sieve or modified 5A molecular sieve as described in claim 3, Cu(I) / 4A molecular sieve or 13X molecular sieve as described in claim 4, and the corresponding adsorbents are cerium molecular sieve adsorbent, Ag + Modified Li-LSX molecular sieve adsorbent, modified NaY molecular sieve adsorbent, modified 5A molecular sieve adsorbent, Cu(I) / 4A molecular sieve adsorbent or 13X molecular sieve adsorbent; According to the direction of gas inflow, the cerium molecular sieve adsorbent, Ag + Modified Li-LSX molecular sieve adsorbent, modified NaY molecular sieve adsorbent, modified 5A molecular sieve adsorbent, Cu(I) / 4A molecular sieve adsorbent and 13X molecular sieve adsorbent are assembled in sequence to obtain an adsorbent group, and then two dehydration beds are respectively set at both ends of the adsorbent group to obtain the composite adsorbent.
6. Use of the composite adsorbent according to any one of claims 1 to 4 in the field of hydrogen recovery.
7. The use of the composite adsorbent as claimed in claim 6 in the field of hydrogen recovery, characterized in that: The hydrogen is hydrogen-rich tail gas, in which hydrogen accounts for more than 40% of the volume, and also includes impurity gases such as O2, H2O, CO, and CO2.
8. The use of the composite adsorbent as claimed in claim 7 in the field of hydrogen recovery, characterized in that: The hydrogen-rich tail gas is chlor-alkali tail gas, coke oven gas or liquefied natural gas hydrogen-rich tail gas.
9. The use of the composite adsorbent in the field of hydrogen recovery as claimed in claim 7, characterized in that: The composite adsorbent is applicable to pressure swing adsorption or rapid pressure swing adsorption technology and is arranged in an adsorption tower or an adsorption tank.
10. A tail gas adsorption tower, characterized in that: The tail gas adsorption tower is provided with the composite adsorbent as described in any one of claims 1 to 4.
Citation Information
Patent Citations
Regular structure adsorbent and application thereof
CN106669636A
Adsorbent for efficiently purifying hydrogen
CN109748242A